“Family” as a Site of Gender and Class Struggles in Catherine Lim’s The Song of Silver Frond - Sri Mulyani; Simon Arsa Manggala; Diksita Galuh Nirwinastu (IAIN MADURA, 2022)
“Family” in The Song of Silver Frond (TSOSF) functions as a site of gender and class struggles to challenge the Chinese yin-yang and nei-wai tradition. Continuities and transformations in Chinese familial practices result from complex socio-cultural-generational dynamics.